2019
DOI: 10.3390/nu11092093
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Helicobacter Pylori Infection in Preschool Children and Young Women Does Not Predict Iron Bioavailability from Iron-Fortified Foods

Abstract: Helicobacter pylori infection is common in low-income countries. It has been associated with iron deficiency and reduced efficacy of iron supplementation. Whether H. pylori infection affects iron absorption from fortified and biofortified foods is unclear. Our objective was to assess whether asymptomatic H. pylori infection predicts dietary iron bioavailability in women and children, two main target groups of iron fortification programs. We did a pooled analysis of studies in women of reproductive age and pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…1). There were eight cross-sectional studies, 15,17,18,[27][28][29][30][31] six RCTs, 13,[32][33][34][35][36] five case-control studies, 12,16,20,21,37 two surveys, 11,38 and one cohort study. 14 Only six studies reported participants' average age, hemoglobin, and serum ferritin levels 14,20,28,29,31,36 (►Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). There were eight cross-sectional studies, 15,17,18,[27][28][29][30][31] six RCTs, 13,[32][33][34][35][36] five case-control studies, 12,16,20,21,37 two surveys, 11,38 and one cohort study. 14 Only six studies reported participants' average age, hemoglobin, and serum ferritin levels 14,20,28,29,31,36 (►Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were of high quality (►Table 3). According to the World Bank classification of economic level, six studies 16,27,[31][32][33]35 with a total sample size of 2,086 were conducted in countries with lower middle incomes. In addition, eight studies 11,14,15,17,28,30,36,38 with a total sample size of 3,990 were from high incomes countries and eight 12,13,18,20,21,29,34,37 with a total sample size of 1,813 were from countries with upper middle incomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Synthese von Hepcidin scheint bei H. pylori-infizierten Kindern mit Eisenmangel eher hochreguliert zu sein [495]. Eine asymptomatische H. pylori-Infektion hat in der Regel keinen Einfluss auf die Eisenabsorption aus der Nahrung [496]. Daher soll in der Initialdiagnostik kein nicht-invasiver Test auf das Vorliegen einer H. pylori-Infektion durchgeführt werden [464].…”
Section: Empfehlung 64 (Geprüf T 2021)unclassified
“…Barry Marshall and Robin Warren first identified H. pylori in 1982. In 1989, the bacterium formerly known as Campylobacter pylori ( C.pyloridis ) was reclassified as H. pylori [ 2 , 3 ]. The proof of concept that H. pylori infection causes gastritis was established through self-experiments involving the ingestion of a bacterial broth, followed by subsequent recovery from gastritis upon eradication of H. pylori , thus verifying Koch's postulates [ 4 ].…”
Section: Introductionmentioning
confidence: 99%